A preparation process of shrinkage-resistant carbon fiber composite material
By modifying hydroxytriazine epoxy soybean oil on carbon fiber and grafting reaction with polyurethane foam, the problems of poor shrinkage resistance and flammability of polyurethane foam materials are solved, and the flame retardant performance and enhancement effect are significantly improved.
Patent Information
- Application Number
- CN202410879167.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-02
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-07-02
AI Technical Summary
Polyurethane foam has poor shrinkage resistance, is flammable and has poor flame retardant properties.
Using hydroxytriazine epoxy soybean oil modified carbon fiber with polyether polyol and polyphenyl polymethylene isocyanate for grafting reaction, enhancing the compatibility and interface bonding strength between carbon fiber and polyurethane foam, and through the introduction of epoxy Soybean oil molecular chains and nitrogen-rich triazine functional groups improve flame retardant properties.
It significantly improves the shrinkage resistance and flame retardant properties of carbon fiber composites, enhances the reinforcement effect of carbon fiber and the compressive strength of polyurethane foam, and reduces the volume shrinkage rate and ultimate oxygen index.
Smart Images

Figure CN118620174B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon fiber composite materials, in particular to a preparation process of a shrinkage-resistant carbon fiber composite material. Background Art
[0002] As a high-performance fiber material with high modulus, high strength and high temperature resistance, carbon fiber is widely used in foam, plastic, rubber and other materials. Improving the compatibility between carbon fiber and the material substrate and improving the interface bonding with the material can make carbon fiber more effective in improving the mechanical and thermal properties of the material. Surface modification of carbon fiber has become a research trend.
[0003] Polyurethane foam has low thermal conductivity, strong thermal insulation, low water absorption, good buffering effect, and has good practical applications in furniture, building panels, cold storage insulation, etc. However, polyurethane foam has poor shrinkage resistance, large shrinkage rate, and is easy to burn and has poor flame retardancy. It usually needs to add flame retardants such as ammonium polyphosphate, halogen flame retardant, and aluminum hydroxide. The flame retardant performance of a single ammonium polyphosphate flame retardant is poor, but compounding it with a carbonizing agent can play a good synergistic flame retardant role. Summary of the invention
[0004] The technical problem solved by the invention is to provide a preparation process of a shrinkage-resistant carbon fiber composite material, thereby solving the problem of low strength and poor shrinkage-resistant performance of polyurethane foam materials.
[0005] The technical solution provided by the present invention is: a preparation process of a shrinkage-resistant carbon fiber composite material: polyether polyol, hydroxytriazine epoxy soybean oil-modified carbon fiber, dibutyltin dilaurate, diethanolamine, ammonium polyphosphate, water, and a foam stabilizer are added into a container, polyphenyl polymethylene isocyanate is added after mixing, and the mixture is stirred and mixed to foam naturally, and when the foam is stable, the material is placed in a heating box for maturation to obtain a shrinkage-resistant carbon fiber composite material.
[0006] Further, the aging is first performed at 60-70°C for 18-36 hours and then at 20-30°C for 5-7 days.
[0007] Furthermore, the mass fraction of the hydroxytriazine epoxy soybean oil modified carbon fiber in the carbon fiber composite material is controlled to be 0.5-3%.
[0008] Further, the preparation process of hydroxytriazine epoxy soybean oil modified carbon fiber is:
[0009] (1) Add 100 parts by weight of chlorinated carbon fiber to a solvent, and after dispersion, add 1400-3000 parts by weight of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and 400-800 parts by weight of triethylamine, react at 50-80°C for 48-72h, filter after the reaction, wash with ethanol, and dry to obtain aminotriazine-modified carbon fiber.
[0010] (2) Adding aminotriazine modified carbon fiber into epoxy soybean oil, reacting, filtering, washing with dichloromethane, and drying to obtain hydroxytriazine epoxy soybean oil modified carbon fiber.
[0011] Furthermore, the solvent in (1) is N,N-dimethylformamide, N,N-dimethylacetamide or dichloromethane.
[0012] Furthermore, in (2), the amount of aminotriazine modified carbon fiber is 100 parts by weight, and the amount of epoxidized soybean oil is 2000-5000 parts by weight.
[0013] Furthermore, the reaction in (2) is carried out at 50-60°C for 12-36 hours.
[0014] Furthermore, the preparation method of the chlorinated carbon fiber is: adding the carbon fiber to a nitric acid solution for acidification to obtain acidified carbon fiber; then placing it in thionyl chloride, and adding N,N-dimethylformamide for chlorination to obtain chlorinated carbon fiber.
[0015] The technical effect of the present invention is as follows: the present invention utilizes 2,4,6-tris(4-aminophenyl)-1,3,5-triazine to react with chlorinated carbon fiber to achieve modification of the carbon fiber surface with a phenyl nitrogen-rich triazine structure and multiple amino groups, and then utilizes the amino group to react with the epoxy group of epoxy soybean oil to obtain hydroxy triazine epoxy soybean oil-modified carbon fiber, and further introduces a large number of hydroxyl groups and epoxy soybean oil molecular chains on the carbon fiber surface.
[0016] The present invention adds hydroxy triazine epoxy soybean oil modified carbon fiber when preparing polyurethane foam, introduces a large number of active hydroxyl groups into the carbon fiber, and can be used as grafting polymerization sites to undergo grafting reaction with polyether polyol and polyphenyl polymethylene isocyanate, thereby chemically bonding the carbon fiber to the polyurethane foam matrix, enhancing the compatibility between the carbon fiber and the polyurethane foam, increasing the interface bonding strength, and making the carbon fiber have a better reinforcement effect.
[0017] The invention introduces epoxy soybean oil molecular chains on the carbon fiber surface to play a plasticizing role, and under the synergistic effect, the compression strength of the polyurethane foam carbon fiber composite material is improved, the volume shrinkage rate of the foam is reduced, and the anti-shrinkage performance of the foam is improved.
[0018] The present invention utilizes 2,4,6-tris(4-aminophenyl)-1,3,5-triazine to graft-modify carbon fibers, and introduces a large number of benzene rings and nitrogen-rich triazine functional groups on the surface of the carbon fibers. The carbon fibers can be used as nitrogen-containing carbonizing agents to form a better nitrogen-phosphorus flame retardant system with ammonium polyphosphate, and have a better synergistic flame retardant effect with the carbon fibers, significantly improving the limiting oxygen index of the polyurethane foam carbon fiber composite material and having better flame retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the reaction mechanism diagram of the preparation of hydroxytriazine epoxy soybean oil modified carbon fiber DETAILED DESCRIPTION
[0020] The present invention is further described below in conjunction with specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0021] Example 1
[0022] (1) Add 0.5 g of carbon fiber to 30 mL of 69% nitric acid solution for acidification, take out the carbon fiber, wash it with water, and dry it to obtain acidified carbon fiber, then place it in 20 mL of thionyl chloride, add 0.6 mL of N,N-dimethylformamide, and chlorinate it at 70°C for 48 hours, take out the carbon fiber, wash it with acetone, and dry it to obtain chlorinated carbon fiber.
[0023] (2) Add 0.5 g of chlorinated carbon fiber to 10 mL of N,N-dimethylacetamide, and after dispersion, add 7 g of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and 2 g of triethylamine, and react at 60 ° C for 48 h. After the reaction, filter, wash with ethanol, and dry to obtain aminotriazine-modified carbon fiber.
[0024] (3) Add 1 g of aminotriazine-modified carbon fiber to 20 g of epoxy soybean oil, react at 50° C. for 12 h, filter, wash with dichloromethane, and dry to obtain hydroxytriazine epoxy soybean oil-modified carbon fiber.
[0025] (4) Add 100 g of polyethylene glycol 1000 as a polyether polyol, hydroxytriazine epoxy soybean oil modified carbon fiber, 0.5 g of dibutyltin dilaurate, 0.7 g of diethanolamine, 15 g of ammonium polyphosphate, 8 mL of water, and 1.2 g of a foam stabilizer (brand silicone oil AK8805) into a container, mix well, add polyphenyl polymethylene isocyanate, and control the molar ratio of polyphenyl polymethylene isocyanate and polyethylene glycol 1000 n(OH) / n(NCO) to 2.5:1. Stir and mix well and allow to foam naturally. When the foam is stable, place the material in a heating box, first mature at 60°C for 24 hours, and then mature at 30°C for 5 days to obtain a shrinkage-resistant carbon fiber composite material, and control the mass fraction of hydroxytriazine epoxy soybean oil modified carbon fiber in the carbon fiber composite material to be 0.5%.
[0026] Example 2
[0027] (1) According to the process of Example 1, acylated carbon fiber was prepared.
[0028] (2) Add 0.5 g of chlorinated carbon fiber to 12 mL of dichloromethane, disperse it, add 11 g of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and 3 g of triethylamine, react at 50 ° C for 72 h, filter it after the reaction, wash it with ethanol, and dry it to obtain aminotriazine-modified carbon fiber.
[0029] (3) Add 1 g of aminotriazine-modified carbon fiber to 40 g of epoxy soybean oil, react at 60° C. for 24 h, filter, wash with dichloromethane, and dry to obtain hydroxytriazine epoxy soybean oil-modified carbon fiber.
[0030] (4) Add 100 g of polyethylene glycol 1000 as a polyether polyol, hydroxytriazine epoxy soybean oil modified carbon fiber, 0.8 g of dibutyltin dilaurate, 0.8 g of diethanolamine, 15 g of ammonium polyphosphate, 10 mL of water, and 0.8 g of foam stabilizer (brand silicone oil AK8805) into a container, mix well, add polyphenyl polymethylene isocyanate, control the molar ratio of polyphenyl polymethylene isocyanate and polyethylene glycol 1000 n(OH) / n(NCO) to 2.6:1, stir and mix well, and foam naturally. When the foam is stable, place the material in a heating box, first mature at 60°C for 24 hours, and then mature at 30°C for 5 days to obtain a shrinkage-resistant carbon fiber composite material, and control the mass fraction of hydroxytriazine epoxy soybean oil modified carbon fiber in the carbon fiber composite material to be 0.5%.
[0031] Example 3
[0032] (1) According to the process of Example 1, acylated carbon fiber was prepared.
[0033] (2) Add 0.5 g of chlorinated carbon fiber to 15 mL of N,N-dimethylformamide, disperse it, add 15 g of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and 4 g of triethylamine, react at 80 ° C for 48 h, filter it after the reaction, wash it with ethanol, and dry it to obtain aminotriazine-modified carbon fiber.
[0034] (3) Add 1 g of aminotriazine-modified carbon fiber to 50 g of epoxy soybean oil, react at 55° C. for 36 h, filter, wash with dichloromethane, and dry to obtain hydroxytriazine epoxy soybean oil-modified carbon fiber.
[0035] (4) Add 100 g of polyethylene glycol 1000 as a polyether polyol, hydroxytriazine epoxy soybean oil modified carbon fiber, 0.7 g of dibutyltin dilaurate, 0.8 g of diethanolamine, 15 g of ammonium polyphosphate, 10 mL of water, and 1.4 g of a foam stabilizer (brand silicone oil AK8805) into a container, mix well, add polyphenyl polymethylene isocyanate, and control the molar ratio of polyphenyl polymethylene isocyanate and polyethylene glycol 1000 n(OH) / n(NCO) to 2.6:1. Stir and mix well and allow to foam naturally. When the foam is stable, place the material in a heating box, first mature at 60°C for 24 hours, and then mature at 30°C for 5 days to obtain a shrinkage-resistant carbon fiber composite material, and control the mass fraction of hydroxytriazine epoxy soybean oil modified carbon fiber in the carbon fiber composite material to be 0.5%.
[0036] Comparative Example 1
[0037] The difference between this comparative example and Example 1 is that when preparing the composite material, the hydroxytriazine epoxy soybean oil-modified carbon fiber is not added.
[0038] (1) Add 100 g of polyethylene glycol 1000 as a polyether polyol, 0.5 g of dibutyltin dilaurate, 0.7 g of diethanolamine, 15 g of ammonium polyphosphate, 8 mL of water, and 1.2 g of a foam stabilizer (brand silicone oil AK8805) into a container, mix well, add polyphenyl polymethylene isocyanate, and control the molar ratio n(OH) / n(NCO) of polyphenyl polymethylene isocyanate and polyethylene glycol 1000 to be 2.5:1. Stir well and allow to foam naturally. When the foam is stable, place the material in a heating box, first mature at 60° C. for 24 h, and then mature at 30° C. for 5 days to obtain a polyurethane foam composite material.
[0039] Comparative Example 2
[0040] The difference between this comparative example and Example 1 is that, when preparing the composite material, ordinary carbon fiber is used instead of the hydroxytriazine epoxy soybean oil modified carbon fiber.
[0041] (1) Add 100 g of polyethylene glycol 1000 as a polyether polyol, carbon fiber, 0.5 g of dibutyltin dilaurate, 0.7 g of diethanolamine, 15 g of ammonium polyphosphate, 8 mL of water, and 1.2 g of a foam stabilizer (brand silicone oil AK8805) into a container, mix well, add polyphenyl polymethylene isocyanate, control the molar ratio n(OH) / n(NCO) of polyphenyl polymethylene isocyanate and polyethylene glycol 1000 to be 2.5:1, stir and mix well, and foam naturally. When the foam is stable, place the material in a heating box, first mature at 60°C for 24 hours, and then mature at 30°C for 5 days to obtain a shrinkage-resistant carbon fiber composite material, and control the mass fraction of carbon fiber in the carbon fiber composite material to be 0.5%.
[0042] Comparative Example 3
[0043] The difference between this comparative example and Example 1 is that when preparing the composite material, aminotriazine-modified carbon fiber is used instead of hydroxytriazine-epoxidized soybean oil-modified carbon fiber.
[0044] (1) Add 100 g of polyethylene glycol 1000 as a polyether polyol, aminotriazine-modified carbon fiber, 0.5 g of dibutyltin dilaurate, 0.7 g of diethanolamine, 15 g of ammonium polyphosphate, 8 mL of water, and 1.2 g of a foam stabilizer (brand silicone oil AK8805) into a container, mix well, add polyphenyl polymethylene isocyanate, control the molar ratio n(OH) / n(NCO) of polyphenyl polymethylene isocyanate and polyethylene glycol 1000 to be 2.5:1, stir and mix well, and foam naturally. When the foam is stable, place the material in a heating box, first mature at 60°C for 24 hours, and then mature at 30°C for 5 days to obtain a shrinkage-resistant carbon fiber composite material, and control the mass fraction of aminotriazine-modified carbon fiber in the carbon fiber composite material to be 0.5%.
[0045] Comparative Example 4
[0046] The difference between this comparative example and Example 1 is that ethylenediamine is used instead of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine when preparing the modified carbon fiber.
[0047] (1) Add 0.5 g of chlorinated carbon fiber to 10 mL of N,N-dimethylacetamide, add 7 g of ethylenediamine and 2 g of triethylamine after dispersion, react at 60 ° C for 48 h, filter after the reaction, wash with ethanol, and dry to obtain amino-modified carbon fiber.
[0048] (2) Add 1 g of amino-modified carbon fiber to 20 g of epoxy soybean oil, react at 50° C. for 12 h, filter, wash with dichloromethane, and dry to obtain hydroxy-epoxidized soybean oil-modified carbon fiber.
[0049] (3) Add 100 g of polyethylene glycol 1000 as a polyether polyol, hydroxy epoxy soybean oil modified carbon fiber, 0.5 g of dibutyltin dilaurate, 0.7 g of diethanolamine, 15 g of ammonium polyphosphate, 8 mL of water, and 1.2 g of a foam stabilizer (brand silicone oil AK8805) into a container, mix well, add polyphenyl polymethylene isocyanate, and control the molar ratio of polyphenyl polymethylene isocyanate and polyethylene glycol 1000 n(OH) / n(NCO) to 2.5:1. Stir and mix well and allow to foam naturally. When the foam is stable, place the material in a heating box, first mature at 60°C for 24 hours, and then mature at 30°C for 5 days to obtain a shrinkage-resistant carbon fiber composite material, and control the mass fraction of the hydroxy epoxy soybean oil modified carbon fiber in the carbon fiber composite material to be 0.5%.
[0050] The limiting oxygen index of composite materials is tested according to GB / T 2406.1-2008. The compression properties of composite materials are tested according to GB / T8813-2020.
[0051] Volume shrinkage S = (C 1 -C 2 ) / C 1 × 100%. C1 is the initial volume expansion rate of the composite material. C2 is the volume expansion rate of the composite material after the foam is stabilized.
[0052] Among them C 1 =P / P 1 . C 2 =P / P 2 . P is the apparent density of the composite material before foaming. 1 is the initial apparent density of the composite foam. 2 It is the apparent density of the composite material after the foam has stabilized.
[0053] The apparent density is tested using an electronic density balance according to the displacement method.
[0054] Table 1 Carbon fiber composite material performance test
[0055]
[0056]
[0057] As shown in Table 1, carbon fiber is not added to the polyurethane foam material of Comparative Example 1, the limiting oxygen index is 23.4%, the compression strength is 0.092 MPa, and the volume shrinkage is 0.162%.
[0058] In embodiments 1, 2, and 3, when polyurethane is foamed, hydroxy triazine epoxy soybean oil modified carbon fiber is added, a large number of active hydroxyl groups are introduced into the carbon fiber, which can be used as grafting polymerization sites, and grafting reaction occurs with polyether polyols and polyphenyl polymethylene isocyanate, so that the carbon fiber is chemically bonded to the polyurethane foam matrix, and the compatibility between the carbon fiber and the polyurethane foam is enhanced, and the interface bonding strength is greater, so that the carbon fiber has a better reinforcing effect, and the epoxy soybean oil molecular chain is introduced on the surface of the carbon fiber, which can play a plasticizing role, and the compression strength of the polyurethane foam carbon fiber composite material is improved under the synergistic effect, and the volume shrinkage of the foam is reduced, and the shrinkage resistance of the foam is improved. Utilize 2,4,6-tris (4-aminophenyl) -1,3,5-triazine to graft and modify the carbon fiber, introduce a large number of benzene rings and nitrogen-rich triazine functional groups on the surface of the carbon fiber, can be used as a nitrogen-containing carbonizing agent, and form a better nitrogen-phosphorus flame retardant system with ammonium polyphosphate, and play a better synergistic flame retardant effect with the carbon fiber, significantly improve the limiting oxygen index of the polyurethane foam carbon fiber composite material, and have better flame retardant properties.
[0059] Compared with Example 1, when preparing the composite material in Comparative Example 2, ordinary carbon fiber is used instead of hydroxytriazine epoxy soybean oil modified carbon fiber. No active hydroxyl group is introduced on the surface of the carbon fiber, and it is impossible to undergo graft polymerization reaction with polyether polyol and polyphenyl polymethylene isocyanate, resulting in the carbon fiber not being chemically bonded to the polyurethane foam matrix, and the compatibility between the two is poor, and the reinforcing effect of the carbon fiber is not effectively exerted. In addition, the surface of the carbon fiber does not contain epoxy soybean oil molecular chains, and the plasticizing effect on polyurethane is not good, resulting in low compression strength of the composite material, large volume shrinkage, and poor shrinkage resistance. In addition, the surface of the carbon fiber does not contain nitrogen-rich triazine groups, and the limiting oxygen index of the polyurethane foam carbon fiber composite material is low, and the flame retardant performance is poor.
[0060] The aminotriazine modified carbon fiber of Comparative Example 3 does not contain epoxy soybean oil molecular chains, and has a poor plasticizing effect on polyurethane. The compressive strength of the composite material is significantly lower than that of Example 1.
[0061] The amino-modified carbon fiber of Comparative Example 4 does not contain nitrogen-rich triazine groups, and the limiting oxygen index of the polyurethane foam carbon fiber composite material is lower than that of Example 1, and the flame retardant performance is poor. In addition, the compressive strength is lower than that of Example 1, which may be because ethylenediamine contains only two amino groups. After grafting the carbon fiber, the amount of amino groups introduced on its surface is small, and the grafting rate with epoxy soybean oil is low. More active hydroxyl groups and epoxy soybean oil molecular chains are not introduced, resulting in fewer grafting polymerization reaction sites between the carbon fiber and the polyether polyol and polyphenyl polymethylene isocyanate, and the reinforcing effect on the polyurethane foam material is poor, and the compressive strength is lower than that of Example 1.
[0062] Add 100g of polyethylene glycol 1000 as a polyether polyol, hydroxytriazine epoxy soybean oil modified carbon fiber, 0.7g of dibutyltin dilaurate, 0.8g of diethanolamine, 15g of ammonium polyphosphate, 10mL of water, and 1.4g of foam stabilizer (brand silicone oil AK8805) into a container, mix well and add polyphenyl polymethylene isocyanate, control the molar ratio n(OH) / n(NCO) of polyphenyl polymethylene isocyanate and polyethylene glycol 1000 to be 2.6:1, stir and mix well and foam naturally, place the material in a heating box when the foam is stable, first mature at 60°C for 24h, and then mature at 30°C for 5 days to obtain a shrinkage-resistant carbon fiber composite material, and control the mass fraction of hydroxytriazine epoxy soybean oil modified carbon fiber in the carbon fiber composite material to be 0.5-3%.
[0063] Table 2 Properties of carbon fiber composites
[0064]
[0065] It can be seen from Table 2 that as the mass fraction of hydroxytriazine epoxy soybean oil modified carbon fiber gradually increases, the limiting oxygen index of polyurethane foam carbon fiber composites becomes larger and larger, and the flame retardant properties become better and better. However, the compression strength and volume shrinkage rate show a trend of first increasing and then decreasing.
[0066] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, combinations and simplifications of these implementation methods without departing from the principles and spirit of the present invention are all included in the protection scope of the present invention.
Claims
1. A process for preparing a shrinkage-resistant carbon fiber composite material, It is characterized in that The preparation process comprises: adding polyether polyol, hydroxytriazine epoxy soybean oil modified carbon fiber, dibutyltin dilaurate, diethanolamine, ammonium polyphosphate, water, and a foam stabilizer into a container, adding polyphenyl polymethylene isocyanate after mixing, stirring and mixing to allow natural foaming, and placing the material in a heating box for aging after the foam is stable, so as to obtain a shrinkage-resistant carbon fiber composite material; The preparation process of the hydroxytriazine epoxy soybean oil modified carbon fiber is as follows: (1) adding chlorinated carbon fiber to a solvent, adding 2,4,6-tris(4-aminophenyl)-1,3,5-triazine and triethylamine after dispersion, filtering, washing, and drying after reaction to obtain aminotriazine-modified carbon fiber; (2) Adding aminotriazine modified carbon fiber into epoxy soybean oil, reacting, filtering, washing, and drying to obtain hydroxytriazine epoxy soybean oil modified carbon fiber.
2. The process for preparing the shrinkage-resistant carbon fiber composite material according to claim 1, It is characterized in that The aging is first performed at 60-70° C. for 18-36 hours, and then at 20-30° C. for 5-7 days.
3. The process for preparing the shrinkage-resistant carbon fiber composite material according to claim 1, It is characterized in that The mass fraction of the hydroxytriazine epoxy soybean oil modified carbon fiber in the carbon fiber composite material is controlled to be 0.5-3%.
4. The process for preparing the shrinkage-resistant carbon fiber composite material according to claim 1, It is characterized in that The solvent in (1) is N,N-dimethylformamide, N,N-dimethylacetamide or dichloromethane.
5. The process for preparing the shrinkage-resistant carbon fiber composite material according to claim 1, It is characterized in that In the method (1), the amount of chlorinated carbon fiber is 100 parts by weight, the amount of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine is 1400-3000 parts by weight, and the amount of triethylamine is 400-800 parts by weight.
6. The process for preparing the shrinkage-resistant carbon fiber composite material according to claim 1, It is characterized in that The reaction in (1) is carried out at 50-80°C for 48-72h.
7. The process for preparing the shrinkage-resistant carbon fiber composite material according to claim 1, It is characterized in that In the (2), the amount of aminotriazine modified carbon fiber is 100 parts by weight, and the amount of epoxidized soybean oil is 2000-5000 parts by weight.
8. The process for preparing the shrinkage-resistant carbon fiber composite material according to claim 1, It is characterized in that The reaction in (2) is carried out at 50-60°C for 12-36 hours.
9. The process for preparing the shrinkage-resistant carbon fiber composite material according to claim 1, It is characterized in that The preparation method of the chlorinated carbon fiber is as follows: adding the carbon fiber into a nitric acid solution for acidification to obtain the acidified carbon fiber; then placing the carbon fiber in thionyl chloride and adding N,N-dimethylformamide for chlorination to obtain the chlorinated carbon fiber.
Citation Information
Patent Citations
Carbon-fiber-reinforced polyurethane foamed plastic and preparation method thereof
CN102558495A
Formula of low shrinkage rate flame-retardant polyurethane hard foam material and method of preparing foam material
CN109593226A
Shear-resistant carbon fiber composite board
CN110093010A
Colored zero-shrinkage carbon fiber reinforced SMC (sheet molding compound) and preparation method thereof
CN115960455A
Carbon fiber-containing radio wave absorber and its manufacturing method
JP6726796B1
